Finasteride treatment alters MMP-2 and-9 gene expression and activity in the rat ventral prostate - Delella, Flávia Karina [UNESP]; Justulin, Luis A. [UNESP]; Felisbino, Sergio L. [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
P>The safety of using finasteride as a prevention of prostate cancer is still under debate. In this study, we investigated the effects of finasteride on the location, gene expression and activities of matrix metalloproteinases -2 and -9, which are involved in the degradation of extracellular matrix components during tissue remodelling and prostate cancer progression, invasion and metastasis. Ventral prostates (VP) from Wistar rats treated with finasteride (25 mg/kg/day) for 7 and 30 days and age-matched controls were evaluated using histology, immunohistochemistry, semi-quantitative RT-PCR and gelatin zymography. Finasteride treatment reduced the epithelial immunostaining of MMP-2 but increased MMP-9 immunostaining in the epithelial cells and in the stroma. The mRNA expression of both MMP-2 and MMP-9 were significantly increased on day 7 of finasteride treatment, mainly for MMP-9 and returned to the control levels by day 30. However, gelatin zymography showed that MMP-9 activity was significantly increased on day 7 of finasteride treatment and remained elevated on day 30 (p < 0.05), while MMP-2 activity was reduced after 30 days of treatment. Finasteride increases MMP-9 and reduces MMP-2 activities in the prostate, which may affect negatively and positively both normal and tumoural prostatic cell behaviour during the treatment. Studies on expression of MMPs in the prostate during different androgen manipulation or cancer chemoprevention strategies can contribute to understand the tissue's overall response and clinical data.
Keywords: apoptosis; finasteride; matrix metalloproteinase; prostate; zymography